Integration of Al-Qur’an Values in Modern Karate Coaching: A Conceptual Literature Study for Athlete Character Development (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Modern sports coaching has experienced significant development by emphasizing not only physical and technical improvement but also athlete character formation and moral development. In karate, character values such as discipline, self-control, honesty, and responsibility are essential components supporting athlete performance and sportsmanship. Therefore, integrating spiritual values, particularly Al-Qur’anic values, into modern karate coaching is considered important in developing holistic athletes with strong moral integrity. This study aimed to analyze the integration of Al-Qur’anic values into modern karate coaching as an effort to develop athlete character. This study employed a literature review method with a conceptual approach. Data sources were collected from scientific journals, sports coaching books, sports psychology literature, and Islamic references discussing Al-Qur’anic values and character education. Literature searches were conducted through several academic databases, including Google Scholar, Scopus, ScienceDirect, and Garuda. Data analysis was performed using content analysis techniques to identify and synthesize Qur’anic values relevant to karate coaching and athlete character development. The findings revealed that several major Qur’anic values, including discipline (istiqamah), patience (sabr), honesty (sidq), responsibility (amanah), hard work (mujahadah), self-control (taqwa), and justice (‘adl), have strong relevance to modern karate coaching principles. These values contribute positively to athlete discipline, emotional regulation, sportsmanship, training motivation, and moral behavior during training and competition. The study also formulated a conceptual coaching model integrating spiritual values into karate training through habituation, role modeling, spiritual motivation, and reflective evaluation. In conclusion, the integration of Al-Qur’anic values into modern karate coaching can become a holistic coaching approach capable of developing athletes who are physically competent, mentally resilient, and morally grounded.